2010
DOI: 10.1080/00423110903456909
|View full text |Cite
|
Sign up to set email alerts
|

Ride comfort enhancement and energy efficiency using electric active stabiliser system

Abstract: This paper introduces the concept of a road input control system to coexist superior ride comfort performance with driving stability using an electric active stabiliser system. The specific road input control system studied, extends the skyhook theory in the roll direction to offer both ride comfort and driving stability. The predictions of performance achieved by this method have been confirmed through actual vehicle tests to offer superior ride comfort and tracing performance. Moreover, consumed power of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…Considering the human body sensitivity to roll vibration (around 0.8 Hz) and roll resonant frequency (around 2 Hz), 13 the power spectral density (PSD) of roll rate in 0.3–3 Hz is used for evaluating vehicle ride comfort. The PSD of vehicle roll rate under J-turn and DLC maneuvers is shown in Figure 24.…”
Section: The Hil Testmentioning
confidence: 99%
“…Considering the human body sensitivity to roll vibration (around 0.8 Hz) and roll resonant frequency (around 2 Hz), 13 the power spectral density (PSD) of roll rate in 0.3–3 Hz is used for evaluating vehicle ride comfort. The PSD of vehicle roll rate under J-turn and DLC maneuvers is shown in Figure 24.…”
Section: The Hil Testmentioning
confidence: 99%
“…To calculate and debug easily, the BLDC motor model is replaced by the direction current (DC) motor model [15] by Eqs. (5) to (8).…”
Section: Asb Actuator Modelmentioning
confidence: 99%
“…It is confirmed that the roll angle control of ASB system shows excellent frequency response characteristics. Considering the human body sensitivity to roll vibration (around 0.8 Hz) and roll resonant frequency (around 2 Hz), the PSD of roll rate in the 0.3 Hz to 3 Hz domain is used to evaluate the vehicle ride comfort [5]. From Fig.…”
Section: Roll Stabilitymentioning
confidence: 99%
“…Other than that, heavy vehicles are also prone to roll over, and implementation of AARB were studied by [6,7]. Passenger cars were also focused by researchers in an attempt to improve ride and handling [1,[8][9][10]. These AARB systems have their own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the system studied by Cech [8] did not utilise any physical ARB, despite being an anti-roll control system. The AARB system studied by Mizuta et al [10] and Kim and Park [1] used more efficient electric actuators. However, the control systems used by them were complex and required detailed mathematical derivation each time when the system is to be adapted into different vehicle model.…”
Section: Introductionmentioning
confidence: 99%